Strategic Framework for Enhancing Food Security and Economic Growth in Tomini Bay’s Agricultural Sector - Yenni Mulyati; Rachman Agus Bahar; Funco Tanipu, Echan Adam (STIE Amkop Makassar, 2024)
Food security ensures consistent access to nutritious food for all people. This study examines the agricultural potential of Tomini Bay, encompassing North Sulawesi, Gorontalo, and Central Sulawesi, with the goal of strengthening regional food security and promoting economic growth. Despite its natural wealth and strategic location, Tomini Bay faces challenges such as limited technological access, inadequate infrastructure, and weak market connectivity. This research applies descriptive quantitative and qualitative approaches, gathering data from key stakeholders, including farmers and officials, from July to December 2023. SWOT, IFAS, EFAS, and QSPM analyses were used to identify the region's strengths, weaknesses, opportunities, and threats. The findings highlight Tomini Bay’s significant assets, such as abundant resources, diverse ecosystems, and governmental support, though infrastructure and technology limitations hinder development. Recommended strategies focus on improving infrastructure, enhancing human resource skills, and leveraging Special Economic Zones and ASEAN market opportunities. These results underscore the importance of collaboration among government, private sectors, and local communities to achieve sustainable agricultural development. This study contributes to Indonesia’s food security framework by offering a region-specific model for integrating agricultural potential with sustainable development goals. Further research should examine climate impacts and explore technology adoption among small-scale farmers.